Analysis of the Influence of Digital Information Quality, Technology Performance Expectancy, Technology Effort Expectancy, Price Value and Social Influence on Intention to Use Coffee Shop Mobile Application - Irwansyah Rezeki, Syailendra Reza; Dharmawan, Donny; Saksono, Lalang; Ekasari, Silvia; Abdurohim (Jurnal Informasi dan Teknologi, 2023)
The Purpose Of This Study Is To Examine How Factors Such As Pricing Value, Habit, Social Influence, Performance Expectancy, Information Quality, And Facilitating Conditions Affect Users' Ongoing Intention To Use Mobile Apps. Researchers Employed A Single Cross-Sectional Design For Data Gathering In This Study, Utilizing A Conclusive Descriptive Research Approach. Mobile Application Users Made Up The Study's Population. Thus, Judgmental Sampling Will Be The Type Of Sampling And Non-Probability Sampling Will Be The Technique Employed. In This Study, 100 Respondents Made Up The Sample. Multiple Linear Regression Analyses Are Used In This Research To Examine Hypotheses. The Continual Intention To Utilize Is Unaffected By The Information Quality Variable. Continuous Intention To Use Is Not Influenced By The Performance Expectation Variable. Continuous Intention To Use Is Not Influenced By The Effort Expectancy Variable. The Ongoing Intention To Use Is Unaffected By The Social Impact Variable. Continuous Intention To Use Is Influenced By The Facilitating Conditions Variable. The Ongoing Intention To Utilize Is Independent Of The Trust Variable. The Ongoing Intention To Use Is Influenced By The Price-Value Variable. The Continuous Intention To Use Is Influenced By The Habit Variable.